The effects of resistance training on explosive strength indicators in adolescent basketball players - Santos, E. J. A. M.; Janiera, M. A. A. S. (The Journal of Strength and Conditioning Research, 2012)
The purpose of this study was to assess the effects of a lower- and upper-body 10-week in-season resistance training program on explosive strength development in young basketball players. Twenty-five adolescent male athletes, aged 14-15 years old, were randomly assigned to an experimental group (EG; n = 15) and a control group (CG; n = 10). The subjects were assessed at baseline and after training for squat jump (SJ), countermovement jump (CMJ), Abalakov test, drop jump, and seated medicine ball throw (MBT). The EG showed significant increases (p < 0.05) in all the variable scores. Conversely, the CG significantly decreased (p < 0.05) in SJ, CMJ, and Abalakov test scores and significantly increased in the results of MBT test (p < 0.05). The groups were similar on pretest, but significant differences (p < 0.05) occurred on posttest in all the variables. The results of this study show that a 10-week in-season resistance training program with moderate volume and intensity loads increased vertical jump and MBT performance in adolescent male basketball players. Coaches should know that such a short resistance training program specifically designed for young basketball players induce increased explosivity levels, which are essential to a better basketball performance, with no extra overload on adolescents' skeletal muscle development.